2009
DOI: 10.3109/07357900902769723
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Expression of Human Arrest-Defective-1 (hARD1) Protein With Breast Cancer

Abstract: Human arrest-defective-1 (hARD1) was reported to be important in regulating cell cycle and promoting lung cancer cell proliferation. Here we have investigated the correlation between hARD1 and breast cancer. Analysis with 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) and flow cytometry (FCM) demonstrated that overexpression of hARD1 was associated with increased proliferation of MCF-7 cell, a human breast cancer cell line. Western blotting and immunohistochemical staining assay showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Overexpression of Naa10 increased cell proliferation in breast cancer cells by promoting the cells to pass the G1/S and G2/M cell cycle checkpoints [141]. HeLa cells depleted for NatA showed a reduced viability due to activation of a p53-dependent apoptosis [143], a phenotype also found in colon carcinoma reporting a p53-independent growth inhibition [144].…”
Section: Naa10 and Naa15 Function As Oncogenesmentioning
confidence: 98%
See 1 more Smart Citation
“…Overexpression of Naa10 increased cell proliferation in breast cancer cells by promoting the cells to pass the G1/S and G2/M cell cycle checkpoints [141]. HeLa cells depleted for NatA showed a reduced viability due to activation of a p53-dependent apoptosis [143], a phenotype also found in colon carcinoma reporting a p53-independent growth inhibition [144].…”
Section: Naa10 and Naa15 Function As Oncogenesmentioning
confidence: 98%
“…Different cancer types and tissue display elevated levels of Naa10 expression including hepatocellular carcinoma [131], colorectal cancer [138,139], lung cancer [139,140], breast cancer [139,141] and prostate cancer [142]. Overexpression of Naa10 was also reported in urinary bladder cancer, breast cancer and cervical carcinoma [139].…”
Section: Naa10 and Naa15 Function As Oncogenesmentioning
confidence: 99%
“…Further studies have shown that ARD1 is present in various species, including the mouse, rat, chimpanzee, and human, and has several variants, playing different roles [3][6]. In humans, human ARD1 235 (hARD1) is the major form, involved in diverse biological processes, such as cell proliferation, differentiation, autophagy, and cancer [7]–[13].…”
Section: Introductionmentioning
confidence: 99%
“…□ S The on-line version of this article (available at http://www.jbc.org) contains supplemental Fig. 1 cancer cell lines, and NatA knockdown results in a decrease in cellular proliferation and induction of apoptosis (15)(16)(17)(18). NATs have therefore become an attractive chemotherapeutic target, further driving the need for a molecular understanding of how these enzymes carry out their functions.…”
mentioning
confidence: 99%